Incidences and influences of device-associated healthcare-associated infections in a pediatric intensive care unit in Japan: a retrospective surveillance study. Issue 1 (December 2015) - Hatachi, Takeshi; Tachibana, Kazuya; Takeuchi, Muneyuki
Abstract Background Device-associated healthcare-associated infections (DA-HAIs) are a major problem in pediatric intensive care units (PICUs). However, there are no data available regarding the incidences of DA-HAIs in PICUs in Japan and their influences on length of PICU stay and mortality. The objective of this study was to investigate the incidences of three common DA-HAIs in a PICU and their influences on length of PICU stay and mortality in Japan. Methods We performed a retrospective surveillance study over 12 months in a single PICU in Japan. First, we investigated the incidences of three common DA-HAIs: central line-associated bloodstream infections (CLABSI), ventilator-associated pneumonia (VAP), and catheter-associated urinary tract infection (CAUTI) by chart review, according to the surveillance definitions of the Centers for Disease Control and Prevention/National Healthcare Safety Network. Second, we compared patient characteristics, morbidity, and mortality between the patients with and without DA-HAIs. Results Of all 426 patients admitted to the PICU, 73 % had a central venous catheter, 75 % had an endotracheal tube, and 81 % had a urinary catheter during their PICU stay; the device utilization ratios per patient-days for these were 0.78, 0.53, and 0.44, respectively. In total, 28 patients (6.6 %) acquired at least one of the three DA-HAIs investigated, with an overall incidence per 1000 patient-days of 11.2. The incidences of CLABSI, VAP, and CAUTI per 1000 device-days were 4.3, 3.5, and 13.6, respectively. The median length of PICU stay for the patients with DA-HAIs was 22.5 days, compared with 2 days for those without DA-HAIs. Although there was no statistical difference, the mortality of the patients with DA-HAIs was 7.1 %, whereas the mortality of the patients without DA-HAIs was 2.3 %. Conclusions This study showed the incidences of three common DA-HAIs in a PICU in Japan, and that they were associated with a longer length of PICU stay.